Maximum Likelihood Estimator of AUC for a Bi-Exponentiated Weibull Model. (1st September 2013) - Chang, Fazhe; Qian, Lianfen
Abstract : For a Bi-Exponentiated Weibull model, the authors obtain a general AUC formula and derive the maximum likelihood estimator of AUC and its asymptotic property. A simulation study is carried out to illustrate the finite sample size performance.